Toxicity assessment of pesticides with no ecotoxicological data to freshwater algae - Gökçe, Selen. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2018., 2018)
Widespread contamination of water bodies by pesticides is indeed a matter of great concern. Therefore, their adverse effects on non-target organisms including algae, invertebrates, and fish should be investigated. In this study, freshwater algal toxicity assay was carried out for 8 pesticides (acetamiprid, acetochlor, boscalid, diclofop, diphenamid, gibberellic acid, ioxynil, and 2,4,5-T) selected from the list of chemicals with no ecotoxicological data recently announced by TUBITAK. The effect of selected pesticides on the growth rate of Chlorella vulgaris was measured using the Organisation for Economic Cooperation and Development (OECD) test number 201. The order of 96-h algal toxicity is acetochlor>ioxynil>diclofop>2,4,5-T. The toxicity value for boscalid could not be determined in its solubility limit. Acetamiprid, diphenamid and gibberellic acid revealed IC50 values > 100 mg/L.The experimental results are compared to the predicted toxicity values of tested chemicals from the literature QSAR models. Also, the toxicity values were predicted from an algaealgae (Chlorella vulgaris -Pseudokirchneriella subcapitata) toxicity relationship. Low correlation was found between the toxicity and hydrophobicity implying that these chemicals exert their toxicity in different mode of action other than baseline toxicity. Global half-life, persistence bioaccumulation and toxicity (PBT) indices were calculated for all chemicals. Boscalid and diclofop were found to be PBT chemicals. The calculated low-toxic-effect concentrations (LOEC, NOEC and IC20) were used in risk assessment and Acute to Chronic Ratio (ACR) were evaluated to control if the ACR values are within the safe level of chemicals set for algae.
Keywords: Freshwater algae.; Pesticides.; Environmental toxicology.